Copy number variants in a population‐based investigation of Klippel–Trenaunay syndrome. Issue 2 (30th November 2016) - Dimopoulos, Aggeliki; Sicko, Robert J.; Kay, Denise M.; Rigler, Shannon L.; Fan, Ruzong; Romitti, Paul A.; Browne, Marilyn L.; Druschel, Charlotte M.; Caggana, Michele; Brody, Lawrence C.; Mills, James L.
Abstract : Klippel–Trenaunay syndrome (KTS) is a rare congenital vascular disorder that is thought to occur sporadically; however, reports of familial occurrence suggest a genetic component. We examined KTS cases to identify novel, potentially causal copy number variants (CNVs). We identified 17 KTS cases from all live‐births occurring in New York (1998–2010). Extracted DNA was genotyped using Illumina microarrays and CNVs were called using PennCNV software. CNVs selected for follow‐up had ≥10 single nucleotide polymorphisms (SNPs) and minimal overlap with in‐house controls or controls from the Database of Genomic Variants. We identified 15 candidate CNVs in seven cases; among them a deletion in two cases within transcripts of HDAC9, a histone deacetylase essential for angiogenic sprouting of endothelial cells. One of them also had a duplication upstream of SALL3, a transcription factor essential for embryonic development that inhibits DNMT3A, a DNA methyltransferase responsible for embryonic de novo DNA methylation. Another case had a duplication spanning ING5, a histone acetylation regulator active during embryogenesis. We identified rare genetic variants related to chromatin modification which may have a key role in regulating vascular development during embryogenesis. Further investigation of their implications in the pathogenesis of KTS is warranted. © 2016 Wiley Periodicals, Inc.